Radioprotective activity of glutathione on cognitive ability in X-ray radiated tumor-bearing mice. (2nd September 2018) - Lu, Lina; Li, Zongli; Zuo, Yanhua; Zhao, Libo; Liu, Bin
ABSTRACT: Objectives : The use of X-ray for therapeutics always raises the problem of radiation hazards to living beings. In this research, we explored the radioprotective activity of glutathione (GSH) on cognitive ability of X-ray radiated tumor-bearing mice.Methods: Forty C57BL/6 mice were chosen to establish the GL261 glioma model and randomly divided into four groups: Model group, X-ray group, Pre-GSH group and Pos-GSH group. Morris water maze test was used to test cognitive ability. Moreover, histopathological observation of hippocampus was observed by hematoxylin and eosin (HE) staining. The protein expression of choline acetyl transferase (ChAT) was measured by western blot, simultaneously the contents of acetylcholinesterase (Ach), superoxide dismutase (SOD), methane dicarboxylic aldehyde (MDA), TNF-α and IL-6 were detected by the respective kit.Results : There was a significant difference in X-ray group of the escape latency from the Model group (P<0.05). Besides, HE staining revealed that nucleus in hippocampus cells were pyknotic, glial cells were hyperplastic and the nerve cells were swelling in X-ray group. In X-ray group the expression of ChAT and Ache were decreased versus Model group. Finally, the cognitive ability in Pre-GSH and Pos-GSH group was enhanced than X-ray group, in which the cognitive ability of Pos-GSH group was higher than the Pre-GSH group.Discussion : X-ray impaired the brain tissues and cognitive ability of tumor-bearing mice. The damages of brain tissues were alleviated by Pre-GSH and Pos-GSH protection and the efficacy of Pos-GSH protection was superior to Pre-GSH protection. Abbreviation Ach: Acetylcholinesterase; GSH: Glutathione; HE: Hematoxylin and eosin; MDA: methane dicarboxylic aldehyde; SOD: Superoxide dismutase; TV: Tumor volume; TW: Tumor weight.